Rebound stridor in children with croup after nebulised adrenaline: does it really exist? - Sakthivel, Muthukumar (Breathe (Sheff), 2019)
Rebound stridor after the use of nebulised adrenaline does not exist http://ow.ly/aoOd30o5lEo